recursos educativos gamificados con ia, para la participación activa en egb - Olave Matamba, Sammy Alexander; Castillo Roblez, Andy Eliceo (Machala, 2025)
Nowadays, technology has become an essential part of our daily lives, facilitating various activities including education where its use seeks to improve the learning process. However, in many classrooms this is still not reflected as teachers continue to apply traditional methods assuming the exclusive role of source of knowledge. This happens because they do not know how the technological tools work or their advantages, which limits their integration in the teaching process. A clear example of this situation is observed in the tenth grade Natural Sciences subject at the “Dr. Juan Henríquez Coello” High School, where digital innovation is still a pending challenge. Therefore, this research aims to analyze the impact of gamified resources with artificial intelligence in the teaching-learning process that contributes to the active participation of the student, through the use of a prototype designed to strengthen various attitudes and improve the acquisition of new knowledge. This research aims to implement the Spatial application, designed to respond to the needs of students, allowing them to incorporate resources effectively through methodological strategies according to the digital era. This application is designed to facilitate the teaching and learning of new content involving AI and gamification, providing a more dynamic and inclusive experience for all students. With the incorporation of these AI resources in Spatial, we seek to awaken active participation in students and serve as an innovative tool for teachers. To achieve this goal, we have incorporated various techniques and methods, highlighting the ADDIE model, which due to its structured approach can also be considered a methodology. This model has allowed us to develop for use in both virtual and face-to-face environments, which has been a significant advantage since the experiences gathered throughout the project were carried out in face-to-face mode. Once the product was built, a first experience was carried out with experts in the subject of Natural Sciences of the institution and specialists in educational technology of the Pedagogy of Experimental Sciences Career. These professionals expressed their satisfaction and made a detailed evaluation of aspects such as content, interface and ease of use. In addition, they provided valuable recommendations for improvement in future implementations. This whole process was recorded in an interview, which showed the importance of their contributions to the improvement of the resource. In the second experience, after implementing the recommended suggestions and corrections, the product was presented to the students so that they could explore and use the educational software. During this phase, students had the opportunity to interact with the tool, thus allowing to evaluate its impact as a didactic resource for active participation. To measure the results, a survey was applied to the students which allowed determining that the Spatial application was well received. In addition, its innovative impact on the subject was evidenced, achieving a more dynamic and participatory experience that increased the motivation and interest of the students. The results obtained in our research, based on the collection of data through a pretest and a posttest, allowed us to compare the performance of the students before and after using the prototype. Based on this analysis, it is concluded that the implementation of gamified resources with AI is an innovative and effective strategy in the teaching-learning process. In addition, it provides teachers with a valuable tool to enrich their classes, while for students it represents a more motivating, interactive and participatory learning opportunity, favoring engagement with the subject.
estudiantes para que pudieran explorar y utilizar el software educativo. Durante esta fase, los alumnos tuvieron la oportunidad de interactuar con la herramienta, permitiendo así evaluar su impacto como recurso didáctico para la participación activa. Para medir los resultados, se aplicó una encuesta a los estudiantes lo que permitió determinar que la aplicación Spatial fue bien recibido. Además, se evidenció su impacto innovador en la asignatura, logrando una experiencia más dinámica y participativa que aumentó la motivación e interés de los estudiantes. Los resultados obtenidos en nuestra investigación, a partir de la recolección de datos mediante un pretest y un postest permitieron comparar el desempeño de los estudiantes antes y después de utilizar el prototipo. Con base en este análisis, se concluye que la implementación de los recursos gamificados con IA es una estrategia innovadora y efectiva en el proceso de enseñanza-aprendizaje. Además, brinda a los docentes una herramienta valiosa para enriquecer sus clases, mientras que para los estudiantes representa una oportunidad de aprendizaje más motivadora, interactiva y participativa, favoreciendo el compromiso con la materia.
Keywords: RECURSOS; INTELIGENCIA ARTIFICIAL; GAMIFICACION; TECNOLOGIA; PARTICIPACION ACTIVA; PEA.